Assessing secondhand smoke using biological markers. Issue 3 (2nd September 2012) - Avila-Tang, Erika; Al-Delaimy, Wael K; Ashley, David L; Benowitz, Neal; Bernert, John T; Kim, Sungroul; Samet, Jonathan M; Hecht, Stephen S
Abstract : Secondhand smoke exposure (SHSe) is a known cause of many adverse health effects in adults and children. Increasingly, SHSe assessment is an element of tobacco control research and implementation worldwide. In spite of decades of development of approaches to assess SHSe, there are still unresolved methodological issues; therefore, a multidisciplinary expert meeting was held to catalogue the approaches to assess SHSe and with the goal of providing a set of uniform methods for future use by investigators and thereby facilitate comparisons of findings across studies. The meeting, held at Johns Hopkins, in Baltimore, Maryland, USA, was supported by the Flight Attendant Medical Research Institute (FAMRI). A series of articles were developed to summarise what is known about self-reported, environmental and biological SHSe measurements. Non-smokers inhale toxicants in SHS, which are mainly products of combustion of organic materials and are not specific to tobacco smoke exposure. Biomarkers specific to SHSe are nicotine and its metabolites (eg, cotinine), and metabolites of 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK). Cotinine is the preferred blood, saliva and urine biomarker for SHSe. Cotinine and nicotine can also be measured in hair and toenails. NNAL (4-[methylnitrosamino]-1-[3-pyridyl]-1-butanol), a metabolite of NNK, can be determined in the urine of SHS-exposed non-smokers. The selection of a particular biomarker of SHSe and the analytic biological medium depends on the scientific or public health question of interest, study design and setting, subjects, and funding. This manuscript summarises the scientific evidence on the use of biomarkers to measure SHSe, analytical methods, biological matrices and their interpretation.